Small Intestine Artery False Aneurysm Embolization - S. A. Prozorov (Неотложная медицинская помощь)
Bleeding from an aneurysm of a small intestine artery is a formidable complication, the treatment remains a difficult problem. In this case, aneurysm embolization is indicated. The aim of the article is to describe the role of embolization in the treatment of bleeding in an elderly patient, to analyze the efficacy and risk. The advantage of the intervention is minimal invasiveness and low blood loss. The presented observation showed the effectiveness of endovascular embolization in the rupture of a pseudo-aneurysm.